A simple, low-cost staining method for rapid-throughput analysis of tumor spheroids. (January 2016) - Eckerdt, Frank; Alvarez, Angel; Bell, Jonathan; Arvanitis, Constadina; Iqbal, Asneha; Arslan, Ahmet D.; Hu, Bo; Cheng, Shi-Yuan; Goldman, Stewart; Platanias, Leonidas C.
Tumor spheroids are becoming an important tool for the investigation of cancer stem cell (CSC) function in tumors; thus, low-cost and high-throughput methods for drug screening of tumor spheroids are needed. Using neurospheres as non-adherent three-dimensional (3-D) cultures, we developed a simple, low-cost acridine orange (AO)–based method that allows for rapid analysis of live neurospheres by fluorescence microscopy in a 96-well format. This assay measures the cross-section area of a spheroid, which corresponds to cell viability. Our novel method allows rapid screening of a panel of anti-proliferative drugs to assess inhibitory effects on the growth of cancer stem cells in 3-D cultures.